ANALISIS PENGARUH FAKTOR VARIABEL MAKROEKONOMI TERHADAP JAKARTA ISLAMIC INDEX (JII) PERIODE 2010 – 2013 - Herni Ali (Signifikan: Jurnal Ilmu Ekonomi, 2014)
The aim of this study is examining the relationship between cointergration and causality levels of Exchange Rate, GDP, BI interest rates and inflation on Islamic Capital Markets. The data used in this study is a quantitative secondary data in the form of time series of the period January 2010 to December 2013. The test were conducted with the approach of multiple regression models with variable index research JII (Y), the exchange rate (X1), GDP (X2) , BI rate (X3) and inflation (X4) as for hypothesis testing performed using SPSS statistical software. From the results obtained by testing the hypothesis that: a positive effect on the exchange rate, positive effect on GDP, interest harga sewa rates BI negative effect and inflation positive effect on JII. Simultanious testing into four macroeconomic variables affect the JII.DOI: 10.15408/sjie.v3i2.2061